A theoretical investigation of the structural, electronic and optical properties of transition metal chalcogenides - Abdulsalam, Mahmud (My University, 2015)
Harvesting renewable energy and the miniaturisation of electronic components are among the major challenges of the 21st century. Transition metal chalcogenides (TMC) have interesting properties that are promising in meeting these challenges. It is therefore important to conduct a systematic theoretical study of the structural, electronic and optical properties of the transition metal chalcogenides as possible components of low dimensional transistors or as solar-energy harvesters. In this work, we present the detailed theoretical investigation of the structural, electronic and optical properties of transition metal chalcogenides MyXz, (where M = Hf, Zr, Tc or Re), (X = S, Se and Te), y and z are integers. The structural properties of TMCs were studied using energy-volume relationship (equation of states (EOS)), equilibrium structural lattice parameters, formation and cohesive energies were extracted from the EOS. Mechanical stability test based on elastic constants and phonon dispersion relation were carried out to determine the strengths of the TMCs against mechanical distortions. The most stable structural congurations were used to investigate electronic properties through partial density of states (PDOS) and band structure analysis. Optical properties (absorption coe cients, refractivity, re ectivity) of some of the TMCs were then computed. Our computations of the structural, electronic and the optical properties were based on density functional theory (DFT). Projector-Augmented wave (PAW) was used to mimic electron-ion interactions and generalised-gradient approximation was used in the exchange correlation functional. Van der Waal's correction terms proposed by Grimme (DFT-D2), Lundqvist and Langreth (vdW-DF) and Tkatchenko- Sche er (vdW-TS) were used to account for long range dispersion forces in addition to PBE and its modi ed version for solids PBEsol. Optical properties were investigated at the many body (GW) and Bethe-Salpeter equation (BSE) levels of approximations. Our results obtained are discussed within the theoretical frame work and compared with experimental and previous theoretical results where available.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, October, 2015.
Keywords: Chalcogenides.